2007
DOI: 10.1128/jvi.00399-07
|View full text |Cite
|
Sign up to set email alerts
|

A Tyrosine-Based Signal Plays a Critical Role in the Targeting and Function of Adenovirus RIDα Protein

Abstract: Early region 3 genes of human adenoviruses contribute to the virus life cycle by altering the trafficking of cellular proteins involved in adaptive immunity and inflammatory responses. The ability of early region 3 genes to target specific molecules suggests that they could be used to curtail pathological processes associated with these molecules and treat human disease. However, this approach requires genetic dissection of the multiple functions attributed to early region 3 genes. The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Using an extensive series of adenovirus deletion mutants, we mapped the viral gene responsible for this effect to an E3 transcript encoding a small membrane protein called RIDα-C2 [48,49]. We have also shown that RIDα-C2 was a resident membrane protein in a novel population of endosomes, where it transiently interacted with EGFRs and re-routed them for degradation [19,50,51,52]. In contrast to the ligand-induced pathway, however, adenovirus-induced EGFR trafficking did not require intrinsic tyrosine kinase activity or receptor ubiquitination [19,53].…”
Section: Introductionmentioning
confidence: 99%
“…Using an extensive series of adenovirus deletion mutants, we mapped the viral gene responsible for this effect to an E3 transcript encoding a small membrane protein called RIDα-C2 [48,49]. We have also shown that RIDα-C2 was a resident membrane protein in a novel population of endosomes, where it transiently interacted with EGFRs and re-routed them for degradation [19,50,51,52]. In contrast to the ligand-induced pathway, however, adenovirus-induced EGFR trafficking did not require intrinsic tyrosine kinase activity or receptor ubiquitination [19,53].…”
Section: Introductionmentioning
confidence: 99%
“…A bacterial expression plasmid encoding glutathione S-transferase (GST) fused to the 30-amino-acid C terminus of RID␣ (RID␣-CT) has been described previously (56). BL21 cells were transformed with GST plasmids and cultured at 37°C to an optical density at 600 nm (OD 600 ) of approximately 0.6, induced with 0.1 mM isopropyl-␤-D-thiogalactopyranoside for 16 h at room temperature, and collected by low-speed centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…These mutations did not have a significant impact on RID␣ binding in an established pulldown assay with a glutathione S-transferase (GST) fusion protein encoding ORP1L binding sequences in the RID␣ C terminus (RID␣-CT) ( Fig. 4C) (56). The roles of FFAT and ORD-lid domains were evaluated in shNPC1-RID␣ cells treated with a 3=-untranscribed-region (3=-UTR)-specific ORP1L siRNA and then reconstituted with siRNA-resistant GFP-ORP1L constructs encoding the wild-type protein or mutant variants with (i) a D478A substitution in the FFAT motif that eliminates VAP binding; (ii) a 4-amino-acid deletion (Δ560 -563) that attenuates the sterol sensing capacity of the ORD-lid downstream of Rab7; and (iii) a dual D478A/ Δ560 -563 substitution ( Fig.…”
Section: Wt Ad2mentioning
confidence: 99%
“…These sets of proteins cling to targeted phosphotyrosine residues and further boost intracellular signalling through numerous pathways. 35,36 3.6. Ras/Raf/mitogen-activated protein kinase pathway…”
Section: Biochemical Pathway Designing For Anti-egfr-irgdmentioning
confidence: 99%